A graph theory approach to the dormitory room placement problem - Sri Efrinita Irwan; Triyana Muliawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
One of the important areas in mathematics is graph theory. A graph is a mathematical structure used to model pairwise relations between objects. The theory of graph can be applied in various problems. The purpose of this paper is to solve the dormitory room placement problem using graph theory approach. In this paper, there are two factors used to determine the student room, i.e. the study program and provincial origin.